A 53-year-old man with a sclerosing rib lesion: A case report. Issue 47 (November 2017) - Bai, Shucai; Zhang, Huafeng; Li, Zhijun; Li, Dong; Li, Hui
Abstract: Rationale: Sclerosing osteomyelitis of Garré is a rare condition that occurs most commonly in tubular bones and the mandible. Its nontypical symptoms, low morbidity, and insidious process make its diagnosis difficult at an early stage. In this article, we reported a case of chronic sclerosing osteomyelitis which occurred in flat bone. Patient concerns: A 53-year-old man was diagnosed with rib sclerosing osteomyelitis of Garré who had an 8-year course of intermittent local pain and swelling, which radiated toward the left side of his chest wall. Chest computed tomography (CT) showed irregular sclerosis of the diaphysis of the 10th rib, with periosteal reaction and narrowing of the medullary cavity, and magnetic resonance imaging (MRI) showed T2 heterogeneous low-signal intensity over the 10th rib. Diagnoses: Based on the features of the clinical signs and radiography and biopsy of the lesion, diagnosis of rib sclerosing osteomyelitis of Garré was made. Interventions: The patient was treated with surgical excision of a 10-cm-long lesion after failed conservative treatment. Outcomes: Postoperatively, the patient achieved good functional recovery at the 10-year follow-up. Lessons: Rib sclerosing osteomyelitis of Garré is an unusual condition and represents a noninfective course in the rib with a low morbidity. The surgical management was successful in relieving the patient's symptom.